Interpersonal childhood adversity and stress generation in adolescence: Moderation by HPA axis multilocus genetic variation. (August 2020) - Huang, Meghan; Starr, Lisa R.
Abstract: Research suggests that childhood adversity (CA) is associated with a wide range of repercussions, including an increased likelihood of interpersonal stress generation. This may be particularly true following interpersonal childhood adversity (ICA) and for youth with high hypothalamic-pituitary-adrenal (HPA) axis-related genetic risk. In the current study, we applied a multilocus genetic profile score (MGPS) approach to measuring HPA axis-related genetic variation and examined its interaction with ICA to predict interpersonal stress generation in a sample of adolescents aged 14–17 ( N = 241, Caucasian subsample n = 192). MGPSs were computed using 10 single nucleotide polymorphisms from HPA axis-related genes ( CRHR1, NRC31, NRC32, and FKBP5) . ICA significantly predicted greater adolescent interpersonal dependent stress. Additionally, MGPS predicted a stronger association between ICA and interpersonal dependent (but not independent or noninterpersonal dependent) stress. No gene–environment interaction (G× E) effects were found for noninterpersonal CA and MGPS in predicting adolescent interpersonal dependent stress. Effects remained after controlling for current depressive symptoms and following stratification by race. Findings extend existing G× E research on stress generation to HPA axis-related genetic variation and demonstrate effects specific to the interpersonal domain.